Girls of the sun [videorecording (DVD)] - Husson, Eva; Husson, Eva; Farāhānī, Gulshīftah, 1983-; Bercot, Emmanuelle, 1967-; Afsin, Erol, 1989- (Contemporary classics (Cohen Media Group)., 2019)
Through the eyes of a French journalist, follows the commander of the "Girls of the Sun", a Kurdish female battalion, as they prepare to take back their village from Islamic State terrorists.